Development of a New Analytical Method for Determination of Veterinary Drug Oxyclozanide by Electrochemical Sensor and Its Application to Pharmaceutical Formulation - Ersin Demir; Hulya Silah (Chemosensors, 2020)
A novel highly selective, sensitive and simple analytical technique was recommended for the investigation of anthelmintic veterinary drug oxyclozanide based on square wave anodic stripping voltammetry (SWASV) by using a carbon paste electrode (CPE). According to the cyclic voltammetric data, the oxidation and electron transfer processes of oxyclozanide were found as irreversible and adsorption-controlled, respectively. The voltammetric anodic peak response was characterized with respect to pH, accumulation potential, accumulation time, frequency and pulse amplitude, etc. Under these optimized experimental conditions, the anodic peak density of oxyclozanide was linear to oxyclozanide concentrations in the range from 0.058 to 4.00 mg/L. The described electrochemical method was successfully carried out for the oxyclozanide in pharmaceutical formulation and tap water with mean percentage recovery of 101.5 % and 102.2 %, respectively. The results of pharmaceutical formulation studies were statistically compared to the high-performance liquid chromatographic method.